PERAN BUMDES DALAM MENINGKATKAN EKONOMI MASYARAKAT DI DESA AYUHULA KECAMATAN DUNGALIYO KABUPATEN GORONTALO - Baderan, Umar Sako; Napu, Budiyanto (Program Studi Akuntansi, 2020)
This study aims to determine how the role of BUMDes in Improving Community Economy in Ayuhula Village, Dungaliyo District, Gorontalo Regency. This research is included in the type of descriptive research with a qualitative research approach. The results of the research show that the active role in the aspect of enhancing the quality of human and community life can be found in this aspect to be able to help socially but economically yet to play a role; In the aspect of strengthening the people's economy as the basis for the strength and resilience of the national economy with BUMDes as its foundation, it is found that BUMDes currently has limited capital so this is quite difficult in doing business expansion; In the apsek trying to realize and develop the economy of the village community, obtained with the limitations owned by BUMDes making it difficult to develop businesses related to the potential of the village: and in the aspect of helping the community to increase their income so as to increase the income and prosperity of the community, found where there is pessimism from the village government that BUMDes managers have not been able to if the businesses in BUMDes have increased.